TINGKAT PERTUMBUHAN BAYI ASI EKSKLUSIF 1-5 BULAN DI KECAMATAN CIBADAK DAN GEGESIK PADA BAKU ANTROPOMETRI WHO BARU - Iman Sumarno (Persagi, 2006)
In 2005, the World Health Organization (WHO) has developed a new anthropometric standard. This standard was aimed to be used as international standard. The standard developed in six countries. Using longitudinal design, the standard developed based on exclusive breastfed babies of high social class non-smoking mothers. Since Indonesia did not participate in the development of the standard it is logic if some scientists questioning the appropriateness of the standard for Indonesia children. Objective: To analyze whether the standard is appropriate for Indonesia by plotting the growth achievement of Indonesian breastfed babies on the new WHO anthropometric standard. Method: The analysis using the data of the study on care pattern of Cibadak and Gegesik babies aged 1-5 month old. The mean length and weight of samples fitted to the WHO anthropometric software. The z scores plotted graphically. Results: The Z score length achievement of the breastfed babies were ranged from - 0.43 to 0.83, and the weight for age ranges from -1.03 to -0.17. The growth of babies was influenced by socioeconomic and sanitation as shown that the babies of Cibadak subdistrict growing better than those of Gegesik subdistrict. Conclusion: The new WHO anthropometric standard was fitted lo be used for assessing growth achievement in this study. [Penel Gizi Makan 2006, 29(2): 63-67]